Together We Rise: The Role of Communication and Community Connectedness in Transgender Citizens' Civic Engagement in the United States. Issue 3 (4th May 2022) - Billard, Thomas J
ABSTRACT: This study examines the influences of online communication, in-person socialization, and degree of community connectedness on transgender citizens' political participation in the United States. Drawing on the 2015 U.S. Transgender Survey, we find that while demographics, socioeconomic status, and political self-efficacy contributed to individuals' civic engagement and political campaign contribution, community connectedness was the single largest predictor of civic engagement and alone accounted for almost as much variance in the measurement of civic engagement as all demographics and socioeconomic status combined. At the same time, we found an unhypothesized mutually causal relationship between community connectedness and civic engagement, suggesting each reinforces the other. We also found evidence in-person communication with other transgender people was a larger predictor of political participation than online communication. Taken together, our results move us beyond the traditional sociodemographic or media-use predictors toward a more socially embedded perspective of civic engagement among marginalized groups, demonstrating the vital significance of connectedness to one's identity-based community.